Local Integration as a Durable Solution? - Ahimbisibwe, Frank; Ingelaere, Bert; Vancluysen, Sarah (Institute of Development Policy, 2017)
Despite multiple attempts over the last 15 years, Uganda has been unable to find a durable solution for a group of approximately 17,000 Rwandan refugees living on its soil. The cessation of their refugee status has been repeatedly postponed and is about to come into effect at the end of December 2017. If invoked, Rwandan refugees will become illegal immigrants under Ugandan law and can face deportation. This paper argues instead that a policy facilitating local integration in the host country, even if not perfect, offers the best outlook for many Rwandan refugees currently residing in Uganda. In addition, taking into account the voices of these Rwandan refugees themselves, the paper analyses which obstacles still need to be overcome before local integration can be a real durable solution. Two suggestions are made. First, it is needed to move towards a situation of inclusive development for both refugee and host populations in order to guarantee socio-economic integration and avoid potential xenophobia and resentment. Second, Uganda’s conflicting laws need to be addressed in order for refugees to acquire citizenship, an essential dimension of local integration as a durable solution.
The Case of Rwandan Refugees in Uganda
Keywords: Local Integration; Uganda; Refugees